Exploratory model of perception of risks in the COVID-19 era - García Lirios, Cruz (Fakultas Ekonomi, Universitas Sanata Dharma Yogyakarta, 2024)
Security have concern authorities and civil society during last years. Different society’s substrates have different perceptions on security. Present document explores reliability and validity of an instrument which measures security perception in bachelor’s students by reviewing seven dimensions: territorial, national, public (government), human, public (self-protection), private and internaut. Accordingly, setting values and residual permitted to accept the null hypothesis significant relationship between the theoretical dimensions with respect to the weighted factors.